Trustworthy Execution on Mobile Devices - Vasudevan, Amit.; McCune, Jonathan M.; Newsome, James; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This brief considers the various stakeholders in today's mobile device ecosystem, and analyzes why widely-deployed hardware security primitives on mobile device platforms are inaccessible to application developers and end-users. Existing proposals are also evaluated for leveraging such primitives, and proves that they can indeed strengthen the security properties available to applications and users, without reducing the properties currently enjoyed by OEMs and network carriers. Finally, this brief makes recommendations for future research that may yield practical and deployable results.
Introduction -- Demand for Applications Requiring Hardware Security -- Desired Security Features -- Available Hardware Primitives -- Isolated Execution Environments -- API Architectures -- Analysis and Recommendations -- Summary.
Keywords: Computer science; Computer communication systems; Computer security; Data encryption (Computer science).; Electrical engineering; Computer Science; Systems and Data Security; Computer Communication Networks; Data Encryption; Communications Engineering, Networks; Electronic books